Crisis Communication in Surakarta's Hotels: Adapting Situational Crisis Communication Theory (SCCT) to the Indonesian Cultural Context Amidst Austerity and MICE Decline - Silvi Aris Arlinda; Sezim Turganbaevna; Fairuza Arindra (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
The hospitality industry in Surakarta has experienced significant pressure due to the government’s budget-efficiency policy and the decline in Meetings, Incentives, Conventions, and Exhibitions (MICE) activities. This situation demands a strategic role from public relations practitioners in managing crisis communication to maintain organizational reputation. This study aims to analyze the crisis communication strategies implemented by hotel public relations officers in Surakarta by comparing the Situational Crisis Communication Theory (SCCT) from a Western perspective with its adaptation to the local Indonesian cultural context. The research employed a descriptive qualitative approach with a comparative case study on Solo Paragon Hotel and Harris Hotel Solo, using in-depth interviews, observation, and analysis of documents and digital media. The findings reveal that both hotels categorized the crisis as a victim and accidental crisis, with the dominant use of the diminish strategy combined with local cultural values such as gotong royong (cooperation), musyawarah (deliberation), rukun (social harmony), tepa selira (empathy), and nguwongke wong (humanizing others). This cultural adaptation resulted in a hybrid crisis communication model that integrates SCCT's theoretical framework with relational communication practices rooted in Javanese culture. The study emphasizes that the effectiveness of crisis communication in Indonesia is highly influenced by cultural sensitivity and offers a theoretical contribution through the Hybrid-Relational Crisis Communication Model as well as a practical contribution for hospitality public relations practitioners in designing contextual, empathetic, and sustainable communication strategies.Industri perhotelan di Surakarta mengalami tekanan yang signifikan akibat kebijakan efisiensi anggaran pemerintah dan penurunan aktivitas MICE (Meetings, Incentives, Conventions, and Exhibitions). Situasi ini menuntut peran strategis dari praktisi hubungan masyarakat dalam mengelola komunikasi krisis untuk menjaga reputasi organisasi. Penelitian ini bertujuan untuk menganalisis strategi komunikasi krisis yang diterapkan oleh praktisi hubungan masyarakat hotel di Surakarta dengan membandingkan Teori Komunikasi Krisis Situasional (SCCT) dari perspektif Barat dengan adaptasinya terhadap konteks budaya lokal Indonesia. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan studi kasus perbandingan pada Solo Paragon Hotel dan Harris Hotel Solo, dengan metode wawancara mendalam, observasi, serta analisis dokumen dan media digital. Hasil penelitian menunjukkan bahwa kedua hotel mengkategorikan krisis sebagai krisis korban dan krisis yang tidak disengaja, dengan strategi dominan menggunakan strategi pengurangan dampak yang dipadukan dengan nilai-nilai budaya lokal seperti gotong royong, musyawarah, rukun, tepa selira, dan nguwongke wong. Adaptasi budaya ini menghasilkan model komunikasi krisis hibrid yang mengintegrasikan kerangka teori SCCT dengan praktik komunikasi relasional yang berakar pada budaya Jawa. Penelitian ini menekankan bahwa efektivitas komunikasi krisis di Indonesia sangat dipengaruhi oleh kepekaan budaya dan memberikan kontribusi teoretis melalui Model Komunikasi Krisis Hibrid-Relasional serta kontribusi praktis bagi praktisi hubungan masyarakat perhotelan dalam merancang strategi komunikasi yang kontekstual, empatik, dan berkelanjutan.